Comparison of Coskun and Lichteinstein hernia repair methods for groin hernia - Dinç, Tolga (Ann Surg Treat Res, 2015)
PURPOSE: Coskun hernia repair technique has been reported to be an effective new fascia transversalis repair with its short-term follow-up results. Our aim is to determine the results of Coskun hernia repair technique and to compare it with Lichtenstein technique. METHODS: At this comparative retrospective study a total of 493 patients, who had groin hernia repair procedure using Coskun or Lichtenstein technique, between January 1999 and March 2010 were enrolled into the study. Patients were reached by telephone and invited to get a physical examination. RESULTS: Out of 493 groin hernia repairs, 436 (88.5%) were carried out by residents and 57 (11.5%) by attending surgeons. Lichtenstein technique was the choice in 241 patients and 252 patients underwent Coskun hernia repair technique. Groin hernia recurrence was detected in 8 patients (3.1%) in Coskun hernia repair group and 7 patients (2.9%) in Lichtenstein group. Comparison of early complication rates in Coskun group (3.9%) and Lichtenstein group (4.5%) showed no significant difference. Late complication rates were significantly higher in Lichtenstein group (1.2% vs. 4.9%). The operation time was shorter in Coskun group (44 minutes) than in Lichtenstein group (60 minutes). Subgroup of patients, whose hernia repair operations were carried out by attending surgeons, had a recurrence rate of 0% and 3.8%, in Coskun group and Lichtenstein group, respectively. CONCLUSION: This study showed that Coskun hernia repair technique has a similar efficacy with Lichtenstein repair, on follow-up.